Vaccine Administration Risk in Guillain-Barré Syndrome: A Systematic Review - Febianisa, Tabitha Afifah; Hadinata, Lalu Gde Gilang Alid; Hunaifi, Ilsa; Amalia, Azka (Jurnal Biologi Tropis, 2025)
Guillain-Barré syndrome (GBS) is a disorder in which the body's immune system attacks the peripheral nervous system due to molecular mimicry, characterized by progressive muscle weakness from distal to proximal. This systematic review examines the relationship between vaccination and the risk of GBS. Epidemiological data indicate that the incidence of GBS after vaccination is very low. Although there is a link between vaccination and GBS in some cases, the risk remains smaller than the risk of GBS due to natural infection with the pathogen. This study emphasizes that the benefits of vaccination in preventing infection outweigh the risk of vaccination causing GBS. Guillain-Barré syndrome (GBS) is a disorder in which the body's immune system attacks the peripheral nervous system due to molecular mimicry, causing muscle weakness that progresses rapidly to paralysis. From this literature review, it can be concluded that the risk of GBS after vaccination is very low and is limited to certain vaccines. Furthermore, GBS cases occur more frequently after viral or bacterial infections than after vaccination, indicating that the benefits of vaccination in preventing infectious diseases far outweigh the risk of causing GBS.